Cerebrovascular Disease and Perioperative Neurologic Vulnerability: A Prospective Cohort Study - Vlisides, Phillip E.; Kunkler, Bryan; Thompson, Aleda; Zierau, Mackenzie; Lobo, Remy; Strasser, Mary O.; Cantley, Michael J.; McKinney, Amy; Everett, Allen D.; Mashour, George A.; Picton, Paul (Frontiers in Neurology, 2019)
Background: Stroke is a devastating perioperative complication without effective methods for prevention or diagnosis. The objective of this study was to analyze evidence-based strategies for detecting cerebrovascular vulnerability and injury in a high-risk cohort of non-cardiac surgery patients. Methods: This was a single-center, prospective cohort study. Fifty patients undergoing non-cardiac surgery were recruited – 25 with known cerebrovascular disease and 25 matched controls. Neurologic vulnerability was measured with intraoperative cerebral oximetry as the primary outcome. Perioperative neurocognitive testing and serum biomarker analysis (S-100β, neuron specific enolase, glial fibrillary acid protein, and matrix metalloproteinase-9) were measured as secondary outcomes. Results: Cerebral desaturation events (an oximetry decrease ≥20% from baseline or <50% absolute value for ≥3 minutes) occurred in 7/24 (29%) cerebrovascular disease patients and 2/24 (8.3%) controls (relative risk 3.5, 95% CI 0.81–15.2; P=0.094). Cognitive function trends were similar in both groups, though overall scores (range: 1500 – 7197) were approximately one standard deviation lower in cerebrovascular patients across the entire perioperative period (-1049 [95% CI -1662, -436], P<0.001). No significant serum biomarker differences were found between groups over time. One control patient experienced intraoperative hypoxic-ischemic injury, but no robust biomarker or oximetry changes were observed. Conclusions: Cerebrovascular disease patients did not demonstrate dramatic differences in cerebral oximetry, cognitive trajectory, or molecular biomarkers compared to controls. Moreover, a catastrophic hypoxic-ischemic event was neither predicted nor detected by any strategy tested. These findings support the need for novel research into cerebrovascular risk and vulnerability.